Kindergarten teachers’ perspectives on media education in Austria - Mohammadpourkachalami Kobra; Kogler-Velich Dagmar (Research on Education and Media, 2024)
Given the importance of teachers’ views and perspectives in promoting media literacy among students and children, this study examines the perspectives of kindergarten teachers in Austria on media education. Data was collected through an online survey of kindergarten teachers who participated in a training. The results show that common approaches to media literacy among kindergarten teachers are protectionist and technical approaches. Critical and reflective approaches to media were rarely mentioned by kindergarten teachers.